Prevalensi Avian Influenza pada Itik Mojosari di Kabupaten Solok Berdasarkan Deteksi Influenza A qRT-PCR - Muhammad Kamil; Yulia Yellita; Bayu Rachman (MASALIQ, 2026)
Although Avian Influenza (AI) has been widely reported as a strategic poultry disease in Indonesia, studies that specifically document AI occurrence based on molecular detection in traditionally raised Mojosari ducks remain relatively limited, particularly in major duck-producing areas in West Sumatra. This study aimed to analyze the occurrence of Avian Influenza in Mojosari ducks in Nagari Cupak, Gunung Talang Subdistrict, Solok Regency, as a basis for strengthening poultry disease control. A quantitative approach with a cross-sectional design was employed, involving 50 Mojosari ducks purposively selected from smallholder farms. Data were obtained through laboratory examination using the Influenza A quantitative reverse transcription–polymerase chain reaction (qRT-PCR) method and were analyzed by calculating prevalence, 95% confidence intervals using the exact binomial method, and a proportion test to assess differences in infection occurrence. The results showed that 90.0% of ducks tested positive for Avian Influenza, with an estimated prevalence of 90.0% (95% CI: 78.2–97.4%), and the difference in proportions between positive and negative ducks was significant (p < 0.001). This high level of occurrence indicates active viral circulation associated with the characteristics of the aquatic agroecosystem, low biosecurity implementation, and traditional systems of duck husbandry and movement. The findings underscore the importance of strengthening laboratory-based surveillance, enhancing biosecurity in smallholder farms, and intensifying control of poultry movement, and they provide practical implications for stakeholders in AI control based on a One Health approach, while also opening opportunities for further studies on environmental and management-related risk factors in duck production. Keywords: Avian Influenza; Mojosari Ducks; qRT-PCR; Prevalence; Veterinary Epidemiology